Subsidies – food security or market distortion - Anton Kostadinov (ikonomičeski i socialni alternativi, 2013)
Support, directed to food producers is aiming at long-term stability in food system. Governments offer many programs supporting farmers. Such as price support, export aid, insurance, disaster aid and etc. However, subsidies are controversial tool for sustaining food security, because of their multidimensional effects. Furthermore, subsidies are sources of inequality not only among farmers nationwide, but also among farmers globally. Inability of developing countries to support their food production provoke inequality among global market participants. Millions of food producers around the world are exposed at price risk, and inability of local government to protect them. Main player on global food market support different level of protectionist policies. Such policies are not the matter of food security, but rather the matter of competitiveness on global market.
Keywords: 330; Farm Subsidies; Agricultural Policy; Commodity Trade; Food Security; Trade Policy